PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA SMA PADA MATERI GERAK LURUS BERBASIS ANDROID MENGGUNAKAN APLIKASI UNITY - Putri, Nesha Kenade; Z Zulirfan, Z Zulirfan; Fakhruddin Z, Fakhruddin Z (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study is to examine the validity of a high schoolphysics learning media in straight motion topics for android using the unity application.This development research used ADDIE model that consists of five stages, namelyAnalysis, Design, Development, Implementation, and Evaluation. However, thisdevelopment research is limited to the development stage. The data in this study arequalitative data in the form of opinions and suggestions as well as quantitative data inthe form of scores given to each item assessed by experts consisting of 5 people, 3 ofthem lecturers of physics education and 2 teachers of high school physics subjects to thelearning media developed. The instrument used by experts in providing assessments isthe expert validation sheet (adapted from Nasir, 2014). Data collection techniques werecollected by giving draft learning media along with assessment sheets to five experts.Furthermore, experts are asked to provide an assessment consisting of opinions andsuggestions for improvement as well as scores for each item using a scale of 1-5. Dataanalysis techniques in the form of expert judgment in the form of suggestions forimprovement (if any) and scores for each item that are then tabulated. Items that have ascore of less than 3 (scale 1-5) by experts, these items must subsequently be revisedaccording to expert improvement recommendations and will be re-assessed by experts.This process continues until all the experts state that all items already have a score of 3,4 or 5. Then the average score of each assessment item is calculated. The results of thelearning media validation obtained are valid in the high category with a score of 4.08consisting of aspects design with a score of 4.12, pedagogic aspects with a score of4.00, content aspects with a score of 4.00, and technical aspects of 4.20.Keywords: Unity, ADDIE Model, Straight Motion, Android-Based Physics Learning